Fiber-reinforced ceramic-based composite material and preparation method thereof

By pretreating inorganic fibers and wrapping them in liquid ceramic precursors, the problems of high preparation cost of fiber-reinforced ceramic matrix composites and low interlayer strength are solved, and low cost and high interlayer strength are achieved. Suitable for applications in extreme high temperature environments.

CN119430972APending Publication Date: 2025-02-14AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411609084.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing fiber-reinforced ceramic matrix composites have high preparation process costs and low interlayer strength, which limits their large-scale application.

Method used

By pretreating the inorganic fibers, removing the sizing agent on the surface, then wrapping and molding in a liquid ceramic precursor, repeated multiple drying and heat treatments, a fiber-reinforced ceramic matrix composite material with high interlayer strength was prepared.

Benefits of technology

The low-cost preparation of fiber-reinforced ceramic matrix composite materials is realized, the interlayer strength of the material is improved, and the insulation and structural materials are suitable for extreme high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430972A_ABST
    Figure CN119430972A_ABST
Patent Text Reader

Abstract

The invention discloses a fiber-reinforced ceramic-based composite material and a preparation method thereof, and belongs to the field of fiber-reinforced ceramic-based composite materials. The method comprises the following steps: pretreating inorganic fibers to remove a sizing agent on the surface; immersing the desized inorganic fiber in a gum dipping pool filled with a liquid ceramic precursor, carrying out winding forming according to a preset track in a drafting state, and winding a cylindrical green body on a cylindrical core mold; cutting the cylindrical green body along a central line on one side in a wetting state, unfolding and flattening to obtain a plate-shaped green body, and drying and thermally treating the green body; and immersing the treated green body into a gum dipping pool filled with a liquid ceramic precursor for gum dipping, then carrying out drying and heat treatment, and repeating the steps for many times to prepare the fiber reinforced ceramic matrix composite material. The preparation method is simple and low in cost, and the prepared material is moderate in interlayer strength and has high temperature resistance, high fracture toughness and high thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fiber reinforced ceramic matrix composite materials, and in particular relates to a fiber reinforced ceramic matrix composite material and a preparation method thereof. Background Art

[0002] Ceramic materials have excellent properties such as high melting point, corrosion resistance, and ablation resistance, but they are brittle and have poor impact resistance. Fiber-reinforced ceramic-based composites inherit the intrinsic properties of ceramic materials while overcoming the shortcomings of ceramic brittle fracture, thereby improving their impact resistance and thermal shock resistance. They are often used as thermal insulation materials and structural materials in military and civilian extreme high temperature environments. For example, silicon carbide fiber-reinforced silicon carbide-based composites are used in aero-engine nozzles and nozzle adjustment plates, and missile nose cones; alumina fiber-reinforced alumina-based composites are used in thermal protection systems of advanced aircraft and aero-engine combustion chamber linings; quartz fiber-reinforced silica-based composites and silicon nitride fiber-reinforced silicon nitride-based composites are used in high-temperature wave-transparent antenna covers of high-speed aircraft.

[0003] At present, the preparation process of fiber-reinforced ceramic-based composite materials is mostly to prepare preforms or green bodies through processes such as layer laying, three-dimensional weaving, winding, etc., and then realize the densification preparation of ceramic-based composite materials through processes such as precursor conversion or reaction infiltration. The composite materials prepared by the weaving process have high interlayer strength and excellent performance, but because the commonly used reinforcing fibers are mostly brittle inorganic fibers, the weaving process mostly relies on manual work, the preparation cycle is long, the fiber utilization rate is low, and the production cost is high. The layer forming process is simple and the cost is relatively low, but the quality control is difficult in the production of large parts. The fiber winding technology has a high degree of mechanization, is easy to realize mechanization and automation, has high production efficiency, and can give full play to the high tensile strength of the fiber. It is used to manufacture products under internal / external pressure, bending, torsion, axial load, etc., so it is widely used in the preparation of fiber-reinforced ceramic-based composite materials. For example, 3M Company of the United States uses the wire laying-winding forming process based on continuous alumina fibers to realize the preparation of semi-conical fiber-reinforced ceramic-based composite materials; DLR of Germany prepared the WHIPOX series of ceramic-based composites through the winding forming process in 2001.

[0004] The preparation of ceramic-based composite materials by winding molding process has been commercialized in the United States, Japan and other countries. Although the process cost has been greatly reduced compared with the composite materials prepared by weaving and laying processes, it is limited by the high cost of raw materials such as continuous silicon carbide fiber and continuous alumina fiber, and the surface of continuous fiber is relatively smooth, the composite interface bonding force is small, and the interlayer strength is low, which limits its large-scale application. Currently, it is only used in a small number of high-end fields such as aerospace. Improving the interlayer performance of composite materials while reducing production costs through process innovation is the key to preparing ceramic-based composite materials by winding molding. Summary of the invention

[0005] An object of the present invention is to provide a fiber-reinforced ceramic matrix composite material having moderate interlaminar strength, high temperature resistance, high fracture toughness and high thermal shock resistance.

[0006] Another object of the present invention is to provide a low-cost method for preparing fiber-reinforced ceramic-based composite materials in order to address the defects or shortcomings in the existing fiber-reinforced ceramic-based composite material preparation technology, which can greatly reduce the production cost of fiber-reinforced ceramic-based composite materials.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a fiber-reinforced ceramic matrix composite material comprises the following steps:

[0009] (1) Pre-treating the inorganic fiber to remove the sizing agent on the surface;

[0010] (2) immersing the desizing inorganic fiber into a dipping tank containing a liquid ceramic precursor, winding the fiber according to a preset trajectory under a drafting state, and winding a cylindrical green body on a cylindrical core mold;

[0011] (3) the cylindrical blank is cut along the center line of one side in a wet state, unfolded and flattened to obtain a plate-shaped blank, and then the blank is dried and heat-treated;

[0012] (4) The green body treated in step (3) is immersed in a dipping tank containing a liquid ceramic precursor for dipping, and then dried and heat treated. This process is repeated multiple times to prepare a fiber-reinforced ceramic matrix composite material.

[0013] Furthermore, the material types of the inorganic fiber in step (1) include but are not limited to one or more of glass fiber, basalt fiber, quartz fiber, alumina fiber, mullite fiber, zirconia fiber, carbon fiber, silicon carbide fiber, and silicon nitride fiber.

[0014] Furthermore, the types of inorganic fibers in step (1) include, but are not limited to, continuous fiber bundles prepared by melt or sol-gel, bundles prepared by chopped fibers or fiber cotton, with a length of not less than 1 meter, preferably with a clean surface, a length of not less than 500 meters, a twist number of not more than 20 twists / meter or untwisted continuous fiber bundles.

[0015] Furthermore, the liquid ceramic precursor in step (2) is a sol, slurry or resin containing one or more metal elements of aluminum, zirconium, magnesium, hafnium and yttrium. The liquid ceramic precursor is liquid at room temperature or after heating, and is transformed into ceramic or crystal after high temperature (800°C) heat treatment, which can wet the fiber filaments.

[0016] Furthermore, the liquid ceramic precursor in step (2) also includes a colloid with a primary particle size of no more than 200 nanometers and a ceramic powder with a particle size of no more than 800 nanometers, and the metal element exists in the form of a metal polymer precursor with a molecular weight less than 20,000.

[0017] Furthermore, the ceramics transformed into by the liquid ceramic precursor after high-temperature heat treatment in step (2) include but are not limited to oxide ceramics composed of one or more of microcrystalline glass, quartz, alumina, mullite, aluminum phosphate, and zirconium oxide, carbide ceramics composed of one or more of silicon carbide, graphite carbon, boron carbide, and zirconium carbide, or nitride ceramics composed of one or more of silicon nitride, boron nitride, and silicon boron nitrogen.

[0018] Furthermore, the cylindrical blank in step (2) is a hollow tube-shaped blank with open ends and a hollow center, and the shapes include but are not limited to a cylindrical shape, a square cylindrical shape or other polygonal cylindrical shapes.

[0019] Furthermore, the wet state in step (3) refers to the state in which the solvent in the system has not completely evaporated after the sol, slurry or resin has been impregnated; or the state in which the substrate has not yet cooled and solidified after the molten liquid has been impregnated, or the state in which the substrate has the ability to flow and be deformed again under the application of force after cooling and solidification.

[0020] Furthermore, the drying in steps (3) and (4) refers to keeping the green body in air, water vapor or inert gas at not less than 40° C. for 20 minutes to 2 days to remove or partially remove the non-ceramic phase components of the green body.

[0021] Furthermore, the heat treatment in steps (3) and (4) includes heating to a temperature range of not less than 500°C (preferably 800-1600°C) in air, water vapor, or an inert gas to completely remove non-ceramic phase components in the green body, thereby rendering the green body in a glassy, ​​ceramic, or crystalline state.

[0022] Furthermore, the heat treatment time in steps (3) and (4) is set according to the type of ceramic. For oxide ceramics, the treatment is performed at a temperature below 1400°C for 5 minutes to 20 hours; for non-oxide ceramics, the treatment is performed at a temperature below 1600°C for 5 minutes to 10 hours.

[0023] Furthermore, in step (4), the green body is mechanically processed, cleaned, and dried to a constant weight after being repeated multiple times to obtain a fiber-reinforced ceramic matrix composite material.

[0024] A fiber-reinforced ceramic-based composite material is prepared by the above preparation method.

[0025] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0026] (1) The fiber-reinforced ceramic matrix composite material prepared by the present invention has high temperature resistance, impact resistance, high fracture toughness, and high thermal shock resistance, and can be widely used as a thermal insulation material and a structural material in the field of extreme high temperature environments.

[0027] (2) The preparation method of the present invention is simple and can be used to prepare plate-shaped, cylindrical and tubular fiber-reinforced ceramic-based composite materials. It has low process cost, short production cycle and is easy to prepare on a large scale.

[0028] (3) The present invention uses filaments prepared by twisting inorganic fiber cotton or filaments composited with continuous fiber yarn as fiber reinforcement, which can greatly reduce the raw material cost of the composite material compared with the existing winding molding process.

[0029] (4) The surface of the fiber cotton twisted filaments used in the present invention is rough, and the fibers can be connected with each other, thereby increasing the friction between the fibers and effectively improving the interlayer strength of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart of the preparation method of fiber-reinforced ceramic matrix composite materials.

[0031] Figure 2 This is a physical picture of a cylindrical alumina fiber reinforced ceramic matrix composite material.

[0032] Figure 3 This is a physical picture of a flat quartz fiber reinforced ceramic matrix composite material.

[0033] Figure 4 This is a physical picture of a long tubular alumina fiber reinforced ceramic matrix composite material. DETAILED DESCRIPTION

[0034] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.

[0035] The following examples specifically implement the method for preparing a fiber-reinforced ceramic matrix composite material proposed in the present invention. The preparation process is as follows: Figure 1 shown.

[0036] Example 1

[0037] The 1.2-meter-long untwisted alumina continuous fiber bundle is pretreated to remove the sizing agent on the surface. The desizing alumina fibers are immersed in a dipping tank containing a liquid ceramic precursor sol containing aluminum elements, a colloid with a primary particle size of 150 nanometers, and a ceramic powder with a particle size of 600 nanometers. The fibers are wound and formed according to a preset trajectory under the stretching state, and a cylindrical blank is wound on a cylindrical core mold. The cylindrical blank is cut along the center line of one side in a wet state, unfolded and flattened to obtain a plate-like blank, and then the blank is kept in air at 40°C for 2 days to remove the non-ceramic phase components of the blank. Then, it is heated to 800°C in air and kept for 10 hours to completely remove the non-ceramic phase components in the blank. Finally, the treated blank is immersed in the dipping tank of the above-mentioned liquid ceramic precursor for dipping, and then the same drying and heat treatment are carried out. This is repeated 5 times, and then mechanical processing, cleaning, and drying to constant weight are carried out to prepare a cylindrical alumina fiber-reinforced ceramic matrix composite material, such as Figure 2 shown.

[0038] Example 2

[0039] The quartz chopped fiber bundle with a length of 500 meters and a twist of 20 / m is pretreated to remove the sizing agent on the surface. The desizing alumina fiber is immersed in a dipping tank containing a liquid ceramic precursor slurry containing zirconium, magnesium elements, a colloid with a primary particle size of 150 nanometers, and a ceramic powder with a particle size of 600 nanometers. It is wound and formed according to a preset trajectory under the drawing state, and a cylindrical blank is wound on a cylindrical core mold. The cylindrical blank is cut along the center line of one side in a wet state, unfolded and flattened to obtain a plate-shaped blank, and then the blank is kept in air at 50°C for 12 hours to partially remove the non-ceramic phase components of the blank. Then it is heated to 500°C in an inert gas and kept for 20 hours to completely remove the non-ceramic phase components in the blank. Finally, the treated green body is immersed in the above-mentioned liquid ceramic precursor dipping tank for dipping, and then the same drying and heat treatment are carried out, and this is repeated 4 times, and then mechanical processing, cleaning, and drying to constant weight are carried out to prepare a flat quartz fiber reinforced ceramic matrix composite material, such as Figure 3 shown.

[0040] Example 3

[0041] Pre-treat the 800-meter-long, 10-twist / meter alumina fiber cotton bundle to remove the sizing agent on the surface. Immerse the desizing alumina fiber in a dipping tank filled with a liquid ceramic precursor slurry containing aluminum, zirconium elements, a colloid with a primary particle size of 100 nanometers, and a ceramic powder with a particle size of 400 nanometers. Wind the fiber according to the preset trajectory under the drawing state, and wind a cylindrical blank on the cylindrical core mold. The cylindrical blank is cut along the center line of one side in a wet state, unfolded and flattened to obtain a plate-shaped blank, and then the blank is kept in air at 60°C for 20 minutes to remove the non-ceramic phase components of the blank. Then, heat it to 1400°C in an inert gas and keep it for 5 minutes to completely remove the non-ceramic phase components in the blank. Finally, the treated green body is immersed in the above-mentioned liquid ceramic precursor dipping tank for dipping, and then the same drying and heat treatment are carried out, and this is repeated 6 times, and then mechanical processing, cleaning, and drying to constant weight are carried out to prepare a long tubular alumina fiber reinforced ceramic matrix composite material, such as Figure 4 shown.

[0042] The performance of the fiber-reinforced ceramic matrix composite material prepared by the present invention (Example 1) and the existing needle suture (2.5D) method was tested. The test results are shown in Table 1.

[0043] Table 1 Performance test data of fiber reinforced ceramic matrix composites

[0044]

[0045] It can be seen from the test data in Table 1 that the fiber-reinforced ceramic matrix composite material prepared by the present invention has the properties of circumferential tensile strength and interlaminar shear strength, and increases the friction between fibers, indicating that the present invention can effectively improve the interlaminar strength of the composite material.

[0046] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a fiber-reinforced ceramic matrix composite material, characterized in that: The following steps are involved: (1) Pre-treating the inorganic fiber to remove the sizing agent on the surface; (2) immersing the desizing inorganic fiber into a dipping tank containing a liquid ceramic precursor, winding the fiber according to a preset trajectory under a drafting state, and winding a cylindrical green body on a cylindrical core mold; (3) the cylindrical blank is cut along the center line of one side in a wet state, unfolded and flattened to obtain a plate-shaped blank, and then the blank is dried and heat-treated; (4) The green body treated in step (3) is immersed in a dipping tank containing a liquid ceramic precursor for dipping, and then dried and heat treated. This process is repeated multiple times to prepare a fiber-reinforced ceramic matrix composite material.

2. The method according to claim 1, characterized in that The material types of the inorganic fiber in step (1) include one or more of glass fiber, basalt fiber, quartz fiber, alumina fiber, mullite fiber, zirconia fiber, carbon fiber, silicon carbide fiber, and silicon nitride fiber.

3. The method according to claim 1 or 2, characterized in that The inorganic fibers in step (1) may be in the form of continuous fiber bundles prepared by melting or sol-gel, or bundles prepared by chopped fibers or fiber cotton, with a length of not less than 1 meter.

4. The method according to claim 1, characterized in that The liquid ceramic precursor in step (2) is a sol, slurry or resin containing one or more metal elements of aluminum, zirconium, magnesium, hafnium and yttrium. The liquid ceramic precursor is liquid at room temperature or after heating, and is converted into ceramic or crystal after high-temperature heat treatment.

5. The method according to claim 4, characterized in that The liquid ceramic precursor in step (2) further comprises a colloid with a primary particle size not greater than 200 nanometers and a ceramic powder with a particle size not greater than 800 nanometers, and the metal element exists in the form of a metal polymer precursor with a molecular weight less than 20,000.

6. The method according to claim 4, characterized in that The ceramics transformed from the liquid ceramic precursor after high-temperature heat treatment in step (2) include oxide ceramics composed of one or more of microcrystalline glass, quartz, alumina, mullite, aluminum phosphate, and zirconium oxide, carbide ceramics composed of one or more of silicon carbide, graphite carbon, boron carbide, and zirconium carbide, or nitride ceramics composed of one or more of silicon nitride, boron nitride, and silicon boron nitrogen.

7. The method according to claim 1, characterized in that The drying in steps (3) and (4) refers to keeping the green body in air, water vapor or inert gas at a temperature not lower than 40° C. for 20 minutes to 2 days to remove or partially remove the non-ceramic phase components of the green body.

8. The method according to claim 1, characterized in that The heat treatment in steps (3) and (4) includes heating to a temperature range of not less than 500°C in air, water vapor or inert gas to completely remove non-ceramic phase components in the green body, so that the green body is in a glassy, ​​ceramic or crystalline state; for oxide ceramics, the heat treatment is performed at a temperature below 1400°C for 5 minutes to 20 hours; for non-oxide ceramics, the heat treatment is performed at a temperature below 1600°C for 5 minutes to 10 hours.

9. The method according to claim 1, characterized in that In step (4), the green body is mechanically processed, cleaned, and dried to a constant weight after being repeated for multiple times to obtain a fiber-reinforced ceramic matrix composite material.

10. A fiber-reinforced ceramic matrix composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Dense precursor belt of SiC fiber-reinforced titanium-based composite and preparation method of dense precursor belt

    CN106521369A

  • Preparation method of alumina fiber reinforced ceramic composite material containing alumina interface layer

    CN112250460A

  • Fiber bundle, three-dimensional woven structure, three-dimensional fabric composite material and technological method

    CN112481773A

  • Lightweight high-pressure-resistant composite pipe, preparation method and preparation system

    CN113650273A

  • Three-dimensional fabric and needling forming method thereof

    CN117183480A